FEA Study on the Stress Distributions in the Polymer Coatings of Cardiovascular Drug-Eluting Stent Medical Devices - Lee, Solki; Lee, Chang Woo; Kim, Chang-Soo (Annals of biomedical engineering, 2014)
Cardiovascular drug-eluting stents (DES) are widely applied medical products to treat diseased narrowed arteries. Despite their wide application, there still are many clinical adverse effects associated with DES implantation. One of the major issues is that the coatings comprised of drug and polymer phases are often delaminated during the deployment of the stent, which can lead to more serious clinical complications. In the present work, we conducted a 3D finite-element analysis (FEA) computational study to quantitatively estimate the stress distributions in the coating components of DES devices. To adequately represent the skeleton design of modern DES products, we adopted the strut geometry of a SYNERGY stent along with a full coating of poly(lactic- co -glycolic) acid. The FEA computation results clearly indicate that the curved regions (i.e., kink) are subject to much higher stress accumulation in the coating. In addition, it was found that the local shear and normal stress distribution profiles in the polymer coatings are different from those based on von-Mises stresses near the kink area.